Selected decontamination methods of chemical warfare agents covered by the Chemical Weapons Convention - Sura, Paweł; Popiel, Stanisław (Biuletyn Wojskowej Akademii Technicznej, 2023)
Decontamination is the overall physicochemical process leading to completely neutralising or weaken-ing the toxic properties of poisonous substances. In the literature, there are many ways to eliminate con-tamination, including more through innovative methods. The decontamination agents known and used so far have been thoroughly tested in terms of interaction with chemical warfare agents (CWA), espe-cially relating to kinetics and the resulting reaction products. However, with the extension of the Chem-ical Weapons Convention to new substances, i.e., compounds of the “A” series, the so-called No-vichoks, their interaction with available decontamination agents is a subject to verification. On the other hand, equally important, new substances find decontaminating applications; therefore, it seems crucial to test them comprehensively regarding their impact on toxic substances. In this paper, selected methods of decontamination of chemical warfare agents are reviewed, together with the experimental results of the conducted research. The main effort was focused on discussing the most essential decontamination agents known so far. Also, attention was paid to new methods of decontamination that have not yet been introduced to common use but only tested in the laboratory for the possibility of use as a decon-tamination agent.Keywords: chemical warfare agents, decontamination, decontamination agents analytical chemistry